Emission Characteristics under Diesel and Biodiesel Fueled Compression Ignition Engine with Various Injector Holes and EGR Conditions - Taejung Kim; Jungsoo Park; Honghyun Cho (Energies, 2020)
The combustion performance of a conventional rail diesel engine was investigated by measuring the exhaust gas with the respect to the number of injector holes, fuel type, and the use of exhaust gas recirculation (EGR), to provide a detailed reduction of environmental pollutants. It was found that a six- or seven-hole injector was more effective than a five-hole injector for reducing the exhaust gas. In addition, the mixing of 20% biodiesel oil with diesel most effectively reduced the HC and NOx contents. The technology generally reduced the NOx and CO contents of the exhaust, but had no significant effect on the HC and CO2 contents.